Mechanistic aspects of the Pd(OAc)n (n = 1–3) catalyzed ethylene acetoxylation: A density functional theory study. (19th August 2022) - Chen, Yamin; Qiu, Pengyuan; Sun, Haoyang; Sun, Li; Liu, Zhen
Abstract : Vinyl acetate is a valuable industrial material used in the production of various polymers. The homogeneous Pd(OAc) n ( n = 1–3) can catalyze ethylene acetoxylation to produce vinyl acetate. However, the reaction mechanism of Pd‐catalyzed formation of vinyl acetate remains unclear, especially in recognizing the active valence states of the Pd center. The full catalytic cycle of Pd‐catalyzed vinyl acetate formation includes ethylene‐acetate coupling, β ‐H elimination, and catalyst regeneration. Based on the Wacker mechanism, two pathways were proposed for the ethylene‐acetate coupling, including a six‐membered ring mechanism through the attack of carbonyl oxygen (O2) of acetate, and a four‐membered ring mechanism through the attack of acetoxy oxygen (O1) of acetate on the coordinated ethylene. Our density functional theory (DFT) calculation shows that PdOAc cannot catalyze the acetoxylation of ethylene to form vinyl acetate due to the presence of a high energetic span. Pd(OAc)2 catalyzed reaction via the six‐membered mechanism is preferred, and the β ‐H elimination is the rate‐determining step. For Pd(OAc)3, the six‐membered mechanism is favored as well, and the ethylene‐acetate coupling is the rate‐determining step. Overall, Pd(OAc)2 showed high activity (path a) toward the formation of vinyl acetate with a calculated TOF of 349 h −1 . Abstract : The full catalytic cycle of Pd(OAc) n ( n = 1–3)‐catalyzed vinyl acetate formation were investigated, including ethylene‐acetate coupling, β ‐H elimination, and catalyst regeneration. Based on the Wacker mechanism, two pathways (path a and path b) were proposed for the ethylene‐acetate coupling, including the attack of acetoxy oxygen (O1) or carbonyl oxygen (O2) of acetate on the coordinated ethylene. DFT calculation shows that Pd(OAc)2 showed high activity (path a) toward the formation of vinyl acetate with a calculated TOF of 349 h −1 .